Insurance Type and Surgical-Patient Characteristics in the UPR-Affiliated Hospitals - Cruz, Norma I.; Santiago, Elvis; Figueroa, Beatriz C. (Puerto Rico Health Sciences Journal, 2020)
Objective: The characteristics of surgical patients were examined according to type of health insurance to determine whether differences existed between these groups. Methods: We evaluated the characteristics of cases in the UPR General Surgery Department’s database (entered from January 1, 2018 through December 31, 2018) by insurance type. The variables examined included age, gender, inpatient/outpatient status, wound classification, type of surgery, American Society of Anesthesiology (ASA) scores and whether a given patient had diabetes, was a smoker, or suffered from hypertension. This database had no trauma cases. Results: Information was available for 5,097 cases during the study period. The mean age of the group was 51 (±22) years. The gender distribution indicated that 56% were women and 44% were men. The insurance types were distributed as follows: government/no insurance, 40%; Medicare, 12%; and private insurance, 48%. The government-insured/uninsured patients were younger (mean age, 41 ±24) and had had emergency surgery more frequently (18%) than had privately insured patients (10%). Medicare patients were significantly older (mean age, 72 ±12), and had had higher incidences of diabetes (46%) and hypertension (81%), presenting with ASA scores greater than or equal to 3 in 73% of cases. More privately insured individuals than those in other groups had had elective surgery (90%); 48% had been outpatients when they had their surgery, 58% had had clean wounds, and 61% of the patients having elective surgery were women. Conclusion: There were significant differences (P<.05) in the characteristics of patients with different types of health insurance. The frequency of emergency surgery was found to be significantly higher in the government-insured/uninsured group than in the privately insured group.